Two new species of the bamboo-feeding planthopper genus Bambusiphaga Huang & Ding from China (Hemiptera, Fulgoromorpha, Delphacidae) - Hong-Xing, Li (Zookeys, 2018)
Abstract. Two new species of the bamboo-feeding genus Bambusiphaga Huang & Ding, 1979, B. yingjiangensis sp. n. and B. ventroprocessa sp. n., are described and illustrated from Yunnan and Hainan, south China. A key to species of the genus are given. A map showing the geographic distribution of the two new species is also provided.